Enhancing sustainable waste management in Raja Ampat: Assessing the waste bank model's effectiveness in the face of socioeconomic challenge - Sidik, Andi Saiful; Wurarah, Rully Novie; Mustiah, Djumiati (Journal of Character and Environment, 2024)
Background: This study investigates the execution and obstacles of waste management in Raja Ampat Regency using the West Bank mechanism, which has been in operation in Waisai City since 2013. The research findings indicate that the primary challenges in the administration of the Waste Bank in Raja Ampat are the recurring turnover of management, resulting in outstanding debts to customers and a significant reliance on support from the local government. Furthermore, the waste segregation method has not been well executed, and the primary incentive for community participation is of the financial kind. Methods: This study employed qualitative approaches to evaluate the efficacy of the Waste Bank model in Raja Ampat Regency. The study was carried out for a duration of six months, specifically from January to June, in Waisai City, which serves as the hub for waste management and tourism endeavors. Findings: Nevertheless, the Waste Bank continues to be the most efficient waste management approach in Raja Ampat Regency. This study suggests implementing enhanced management practices and providing ongoing coaching, along with fostering greater collaboration between the Environmental Agency and pertinent government departments, in order to enhance community engagement. Conclusion: It is suggested that educating people about the significance of waste segregation and engaging the Government Bank as a custodian of consumer funds are further steps to enhance efficiency. The objective of this research is to offer practical assistance to local governments and other stakeholders on how to adopt waste management strategies that are both more effective and sustainable in tourism zones. Novelty/Originality of this Study: The novelty of this study lies in its focus on the implementation and challenges of the Waste Bank model in Raja Ampat, a region heavily impacted by tourism and population growth. By highlighting the unique socio economic hurdles and the importance of community engagement, this research provides practical insights for enhancing sustainable waste management in similar tourism-dependent areas.